1989
DOI: 10.1007/bf00058142
|View full text |Cite
|
Sign up to set email alerts
|

Photographic observations of the cloud in the neighbourhood of libration point L 5 of the Earth-Moon system

Abstract: The paper contains results of three-colour photographic observations of positions and brightness of the cloud in the vicinity of the Earth-Moon libration point Ls. The real character of the images obtained is confirmed by an agreement of their positions on different plates exposed at the same time. The colours of the cloud obtained are essentially different from those of the counterglow. The clouds appeared to be much redder than the counterglow, which may indicate that the particles constituting them are of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Smith et al 1982; Yoder et al 1983; Yoder, Synnott & Salo 1989). Another example of a Trojan configuration closer to home is provided by the extensive dust clouds in the neighbourhood of the L 5 point of the Earth–Moon system claimed by Winiarski (1989).…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al 1982; Yoder et al 1983; Yoder, Synnott & Salo 1989). Another example of a Trojan configuration closer to home is provided by the extensive dust clouds in the neighbourhood of the L 5 point of the Earth–Moon system claimed by Winiarski (1989).…”
Section: Introductionmentioning
confidence: 99%
“…Such a pioneer photographical documentation has been first performed by Kordylewski (1961). According to the other above-mentioned successful trials (Vanysek 1969;Roach 1975;Winiarski 1989), the KDC can be visually detected only from small phase angles (determined by the observer, the Sun and the L4/L5 point), i.e. at or near "full dust moon".…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the data from the Rutgers OSO-6 Zodiacal Light Analyzer experiment, Roach (1975) concluded that these dust clouds do exist in the L4 and L5 points, their angular size is about 6 o as seen from the Earth, and they move around the libration points. Using a number of parallel cameras at the observing station Roztoki Górne, Winiarski (1989) determined that the colours of the dust clouds near the L4 and L5 points differ from those of the counterglow (gegenschein), which means that the dust particles constituting them are also different.…”
Section: Discussionmentioning
confidence: 99%
“…With the help of the Orbiting Solar 40 Observatory, Roach also detected the KDCs in 1975 [12]. In 1989, the clouds were again photographed by Winiarski [13]. On the other hand, many scholars are strongly skeptical about the existence of the KDCs (Roosen, Harrington & Jeffreys 1967; Bruman 1969; Valdes & Freitas 1983; Igenbergs et al 2012) [14].…”
Section: Current Observation Status Of the Kdcsmentioning
confidence: 99%